HOW FINANCIAL PERFORMANCE IS INFLUENCED BY ADAPTATION TO FINANCIAL TECHNOLOGY AND CYBER GOVERNANCE - lisnawati, lisna (Unversitas Prof. Dr. Moestopo (Beragama), 2024)
Financial performance represents the success of a financial institution in managing its business without ignoring external factors in the era of technological disruption. This research aims to examine the influence of financial technology adaptation and cyber governance on financial performance in financial institutions. Quantitative methods are used in this research, with content analysis data collection techniques for 94 banking observation data contained on the Indonesia Stock Exchange (BEI) in 2022 and 2023. Based on the structural test of the PLS SEM model, the results show that financial technology adaptation has a significant positive effect on financial performance. while cyber governance has no influence on financial performance. The limited number of banks that disclose cyber governance is a major limitation in this research. The empirical implication of this research is the use of dimensions of fintech adaptation and cyber governance as assessment measuring tools. Empirical implications for dimensions of fintech adaptation that are suitable as measuring tools include ATM banking, online banking and mobile banking. Empirical implications for cyber governance dimensions include the proportion of independent board of commissioners, institutional ownership, audit committee, managerial ownership and artificial intelligence. The practical implication that can be implemented by financial institutions is that there is a need to improve cyber governance to anticipate cyber crime and scammer crimes in the long term through the use of artificial intelligence in the era of digitalization 4.0 towards 5.0..